Performance Improvement of a Boost Converter Driving a Separately Excited DC Motor using Inductor-Capacitor (LC) Filter. - Usman, H. M.; Olarinoye , G. A.; Saminu, S.; Ibrahim, S.; Mahmud, S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The increasing use of boost converter circuits for driving DC motors is attributed to their ability to provide extensive adjustable speed control, frequent starting, precise speed regulation, braking, and reversing capabilities. However, the presence of harmonic content poses a significant challenge for these converters. This study investigates the performance enhancements achieved through the integration of an Inductor-Capacitor (LC) filter in a boost converter circuit driving a separately excited DC motor. Simulation results demonstrate significant improvements in both converter and motor performance with the LC filter. The average output voltage and current of the converter increase from 122.61 V and 31.24 A to 129.30 V and 34.39 A, respectively, indicating effective ripple mitigation. Additionally, the motor speed rises from 1103 rpm to 1205 rpm, with corresponding improvements in efficiency for both the converter (from 81.21% to 94.18%) and the motor (from 68.32% to 85.13%) with the LC filter. These improvements highlight the critical role of the LC filter in reducing losses, enhancing motor performance, and achieving overall system efficiency gains. These findings highlight the significance of innovative filtering techniques in optimizing power electronics systems and motor control applications.